Sediment exchange to mitigate pollutant exposure in urban soil. (15th May 2018) - Walsh, Daniel; Glass, Katherine; Morris, Samantha; Zhang, Horace; McRae, Isabel; Anderson, Noel; Alfieri, Alysha; Egendorf, Sara Perl; Holberton, Shana; Owrang, Shahandeh; Cheng, Zhongqi
Abstract: Urban soil is an ongoing source for lead (Pb) and other pollutant exposure. Sources of clean soil that are locally-available, abundant and inexpensive are needed to place a protective cover layer over degraded urban soil to eliminate direct and indirect pollutant exposures. This study evaluates a novel sediment exchange program recently established in New York City (NYC Clean Soil Bank, CSB) and found that direct exchange of surplus sediment extracted from urban construction projects satisfies these criteria. The CSB has high total yield with 4.2 × 10 5  t of sediment exchanged in five years. Average annual yield (8.5 × 10 4  t yr −1 ) would be sufficient to place a 15-cm (6-in.) sediment cover layer over 3.2 × 10 5  m 2 (80 acres) of impacted urban soil or 1380 community gardens. In a case study of sediment exchange to mitigate community garden soil contamination, Pb content in sediment ranged from 2 to 5 mg kg −1 . This sediment would reduce surface Pb concentrations more than 98% if it was used to encapsulate soil with Pb content exceeding USEPA residential soil standards (400 mg kg −1 ). The maximum observed sediment Pb content is a factor of 42 and 71 lower than median surface soil and garden soil in NYC, respectively. All costs (transportation, chemical testing, etc.) in the CSB are paid by the donor indicating that urban sediment exchange could be an ultra-low-cost source for urban soil mitigation. Urban-scale sediment exchange has advantages over existing national- or provincial-scale sediment exchanges because it can retain and upcycle local sediment resources to attain their highest and best use (e.g. lowering pollutant exposure), achieve circular urban materials metabolism, improve livability and maximize urban sustainability. Highlights: The NYC Clean Soil Bank (CSB) is a sediment exchange that transfers surplus clean sediment between construction sites. The CSB has high yield with 4.2 × 10 5 t of sediment exchanged in 5 years . Exchanged sediment is an ultra-low-cost cover material that can be used to eliminate pollutant exposure in urban soil . CSB sediment cover of soil with Pb content exceeding USEPA residential soil standards would reduce Pb content by over 98. Urban sediment exchange can achieve circular urban materials metabolism and upcycle sediment to attain its highest uses.